AGILE GOVERNANCE IMPLEMENTATION IN THE GADGET MOBILE APPLICATION FOR LICENSING ADVERTISING IN BANDUNG CITY - Fajarwati, Arnia; Az-zahra , Nasywa Dewanti (Journal of Indonesian Rural and Regional Government, 2023)
This study examines the implementation of Agile Governance in the Gadget Mobile Application (GAMPIL) for the Advertising License Program in Bandung City. The GAMPIL application, developed by the Investment and One-Stop Integrated Service Office, aims to simplify the licensing process for businesses and citizens by allowing them to access services via smartphones, reducing the need for in-person visits. The application aligns with Bandung’s e-Government initiative, designed to streamline services and improve efficiency. Through a qualitative descriptive approach, including observations, interviews, and document analysis, the study assesses the effectiveness of GAMPIL in supporting agile governance principles and meeting public needs. The findings show that while GAMPIL offers convenience, its implementation has not yet reached its full potential. Technical issues, such as system errors and data security concerns, hinder the application’s effectiveness. Public awareness of the application is also low, due to insufficient outreach efforts, limiting user engagement. Additionally, the DPMPTSP struggles with responsiveness and feedback management, key aspects of Agile Governance. The lack of clear communication and slow response to complaints has prevented the application from evolving to meet user needs. Despite these challenges, the study concludes that GAMPIL has the potential to improve the licensing process but requires improvements in user education, system performance, and inter-agency coordination. Strengthening these areas will ensure that the application is more efficient, accessible, and responsive to public demands, making it a more effective tool in the city’s e-Government strategy.